2010
DOI: 10.4218/etrij.10.0109.0300
|View full text |Cite
|
Sign up to set email alerts
|

Wound-State Monitoring for Burn Patients Using E-Nose/SPME System

Abstract: Array‐based gas sensors now offer the potential of a robust analytical approach to odor measurement for medical use. We are developing a fast reliable method for detection of microbial infection by monitoring the headspace from the infected wound. In this paper, we present initial results obtained from wound‐state monitoring for burn patients using an electronic nose incorporating an automated solid‐phase microextraction (SPME) desorption system to enable the system to be used for clinical validation. SPME pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 11 publications
0
42
0
Order By: Relevance
“…An e-nose based on an array of metal-oxide semiconductor sensors was used to monitor bacterial volatiles in the headspaces from swabs and dressings taken from infected wounds and from uninfected swabs. Principal component analysis showed that volatile profiles identified from dressings of infected wounds may be used to discriminate infected from uninfected patients (128). In particular, reportedly, patterns of volatiles released from dressings of chronic wounds can be used to monitor the progress of wound healing (129).…”
Section: Other Infectionsmentioning
confidence: 99%
“…An e-nose based on an array of metal-oxide semiconductor sensors was used to monitor bacterial volatiles in the headspaces from swabs and dressings taken from infected wounds and from uninfected swabs. Principal component analysis showed that volatile profiles identified from dressings of infected wounds may be used to discriminate infected from uninfected patients (128). In particular, reportedly, patterns of volatiles released from dressings of chronic wounds can be used to monitor the progress of wound healing (129).…”
Section: Other Infectionsmentioning
confidence: 99%
“…Early results from that project have shown good differentiation between P. aeruginosa and S. aureus cultures 19 . Using a principal component analysis that was added later in the project to analyse the resultant VOC spectrum, the instrument has also been shown capable of differentiating between infected and uninfected burns by preconcentrating VOCs from swabs and wound dressing materials 40 . The WOUNDMONITOR has unfortunately not matured into commercial technologies, but have provided a scientific basis for the feasibility of applying e-nose technology in wound infection assessment.…”
Section: Detection Of Wound Smells By Electronic Nose Technologymentioning
confidence: 99%
“…For example, Byun and associates 37 developed an e-nose that incorporated an automated solid-phase microextraction desorption system. Th is method allowed recognition of 3 bacteria species at the early stage of wound infection.…”
Section: Techniques For Assessing Wound Odormentioning
confidence: 99%